Perancangan Interior Showroom Mitsubishi di Samarinda - Mariana Wibowo, Raymond Aditya (Intra, 2016)
Nowadays, four-wheeled vehicle with the brand of Mitsubishi are not that well known to people of Samarinda. Two of the main reasons are, there are many other brands that are more popular than Mitsubishi and also the dull interior design of the showroom. Those issues then heavily affect the showroom sales of Mitsubishi. To overcome this issue, an intriguing design for the showroom is needed for Mitsubishi to make the brand stands out from its competitors.This showroom interior design of Mitsubishi in Samarinda presents the modern contemporary style composed with a âFun and Cozyâ concept that will make the showroom gives a distinguished impression and unique characteristic to customers in Samarinda. The use of natural materials will add to the modern contemporary style and also to help make the users, mainly customers and staffs, to feel extra comfortable during their visits and working hours.The design process of the showroom starts with the programming phase that includes the field data gathered from surveys and interview with the owner of the showroom. Then next is the making of design schematic, and finished with the final design phase.